2006
DOI: 10.1517/13543784.15.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Arzoxifene: the development and clinical outcome of an ideal SERM

Abstract: Hormone-sensitive tumours are among the most common cancers in women. Specific inhibition of the estrogen receptor by selective estrogen receptor downregulators or selective estrogen receptor modulators (SERMs) is effective for the treatment of breast and endometrial cancers and may be used for the prevention of breast cancer. Due to differential recruitment of co-activators and corepressors, SERMs are tissue specific and may have antiestrogenic effects in some tissues, with estrogen agonist activity in others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 62 publications
0
23
0
1
Order By: Relevance
“…A recent genome-wide location analysis of AIB1 chromatin affinity sites in 17β-estradiol (E2) -treated MCF-7 cells demonstrated a significant overlap of AIB1 with FoxA1 binding sites in the breast cancer cell DNA (171). FoxA1 is another member of the forkhead family and a determining factor for estrogen receptor function and endocrine response (172). It would be interesting to investigate the portion of AIB1 genomic binding sites that are also engaged by FoxG1, and to determine whether such a population represent a subset of FoxG1-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent genome-wide location analysis of AIB1 chromatin affinity sites in 17β-estradiol (E2) -treated MCF-7 cells demonstrated a significant overlap of AIB1 with FoxA1 binding sites in the breast cancer cell DNA (171). FoxA1 is another member of the forkhead family and a determining factor for estrogen receptor function and endocrine response (172). It would be interesting to investigate the portion of AIB1 genomic binding sites that are also engaged by FoxG1, and to determine whether such a population represent a subset of FoxG1-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data has shown favorable estrogenic effects on bone and lipid metabolism, while exerting antiestrogen effects on breast and uterine tissue [174]. In fact, preclinical studies which compared equivalent doses of arzoxifene, tamoxifen, and raloxifene showed arzoxifene inhibits tumor growth to a greater extent than the other two agents [170,172,177,178].…”
Section: Arzoxifenementioning
confidence: 99%
See 3 more Smart Citations